Sociocultural Networks and Political Participation: A Communication Model for First-Time Voters in Indonesia - Ratna Setyarahajoe; Tri Prasetijowati; Ernawati Huroiroh; Delmarrich Bilga Ayu (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2026)
Low voter turnout is an indicator of voter apathy in exercising their right to vote. The national voter turnout target is estimated at 79.5%, achievable if the abstention rate does not exceed 20.5%. The objective of this study is to develop a model for first-time voter participation through a communication strategy based on sociocultural networks for the 2024 general elections. A purposive sampling method was used in this study. Data were collected through interviews and questionnaires. The results showed that, among 111 respondents, 41% received information about the presidential elections and presidential candidates through social media. A total of 97% declared their intention to exercise their right to vote. Social media plays a crucial role as an intercultural social communication strategy for first-time voters. They use social media posts as a medium for discussion with their friends (51%), family (20%), and organizations (7%). Others follow discussions on WhatsApp groups, Twitter, Instagram, and Facebook. The results of this study show that, for the first time, it is possible to improve the development of electoral participation patterns by using social media as a communication strategy, creating shorter but clearer, simpler, more streamlined, and more attractive messages.